PERJANJIAN TERAPEUTIK SEBAGAI DASAR BAGI DOKTER DALAM MEAKUKAN PENANGANAN MEDIS - Sabir Alwy; Afdhal Afdhal (Universitas Borneo Tarakan, 2019)
AbstractThis research aims to determine the relationship between doctor and patient in a therapeutic agreement, as provided for in Informed Consent and the law of medical practice for doctors and patients understand the obligations and responsibilities as well as provide insights for health professionals, especially physicians about the importance of treaties in creating therapeutic medical services appropriate to the patient.The research was conducted at two hospitals in the city of Makassar is Wahidin Sudirohusodo Hospitals and Hospitals Grestelina. Primary data collection instruments and interviews conducted with the data sender done with literature study and data collection at two institutions. Data were analyzed qualitatively.The results showed that the Therapeutic relationship that occurs between doctor and patient is currently well underway with the hospital where doctors and Grestelina Wahidin Sudirohusodo been clearly understood to provide information needed by patients from both phases of history, diagnosis/ so that everything recorded in prognosis medical records. The patient could complain of illness, but patients tend to be resigned to that advice from doctors is not done. Doctors and hospitals Wahidin Sudirohusodo Grestelina has done its responsibility in caring for patients with always do a routine for inpatients and how to be polite and respect the limits of its competence by following per under the oath that doctors say. Patients have appreciated doter with trying to provide honest information in which the function of creating belief between doctor and patient. Sudirohusodo Wahidin hospital doctors and medical services Grestelina have done in the form of counseling to the patient in choosing the appropriate medication and treatment conditions quickly for emergency room patients are by the SOP (Standard Operating Procedure). SOP (Standard Operating Procedure also regulates every doctor who wants to practice in the hospital, and Grestelina Wahidin Sudirohusodo must have the STR (letter of registration) and SIP (Permit Practice) through the provisions made by the Institute COUNCIL (Physician Discipline Committee) and the Organization of Ethics.